Registro de saberes ancestrales relacionados con las curaciones en los habitantes de las comunidades Balcashi y Puelazo de la parroquia Quimiag. - Haro Donoso, Sandra Ximena (2018)
This research has the objective of registering the ancestral knowledge of the inhabitants of the Balcashi and Puelazo communities fom Quimiag parish, related to the use of medicinal plants and elements of nature, thus strengthening their characteristic identity of this collectivity, being these practices considered as part of intangible cultural heritage, it is appropriate to use the official INPC methodology. To carry out the research and achieve the established objectives, the qualitative method was used since none of the variables were manipulated and it was limited to direct observation of the phenomenon, the study of cases allowed to know the uses of the plants, ceremonies and rites carried out by experts in ancestral knowledge and the use of elements of nature, the type of research correspond to a descriptive and documentary process that allowed to record, analyze and describe the traditional uses of plants and their medicinal properties in order to revalue them. There from this study we can conclude that the ancestral knowledge concerning the ceremonies, rites and practices of ancestral medicine are kept in force, the main entities that know this type of knowledge are the so-called healers, midwives and sinks, who have a wide wisdom to diagnose and prevent them diseases, as well as symptoms related to physical and spiritual well-being.